Algae‐based biostimulants increase yield and quality of mini tomatoes under protected cultivation. Issue 4 (9th March 2022) - de Paula, Bruno Santos; Feltrim, Daniela; Engel, Daniele Caroline Hörz; Baptistella, João Leonardo Corte; Rodrigues, Mayara; Engel, Eduardo; Mazzafera, Paulo
Abstract: Background: Plant biostimulants are organic products primarily based on algae, microorganisms, fulvic and humic acids, proteins, and amino acids, which improve physiological plant performance, leading to increased crop productivity. In this work, commercial algae extract of Ascophyllum nodosum were sprayed on Sweet Heaven mini tomato variety [algae extract 0.5 L ha −1 (AE1) and 2 L ha −1 (AE2); aqueous solution prepared with A. nodosum powder at 1% (w/v) (DA1) and 3% (w/v) (DA2)] growing under greenhouse conditions. Results: Algae treatment significantly affected the yield, diameter, length, color, and Brix degree of the fruits. Fruit volume and weight and the number of cracked fruits did not change. The treatment of mini tomato plants with DA1 led to a higher fruit yield compared to other treatments and untreated plants. Conclusion: Therefore, A. nodosum extract can be an interesting sustainable practice to increase the productivity of mini tomatoes growing under protected conditions.